2011
DOI: 10.1177/0269215511416383
|View full text |Cite
|
Sign up to set email alerts
|

Effects of robot-assisted upper limb rehabilitation on daily function and real-world arm activity in patients with chronic stroke: a randomized controlled trial

Abstract: Symmetrical and bilateral robotic practice, combined with functional task training, can significantly improve motor function, arm activity, and self-perceived bilateral arm ability in patients late after stroke.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
126
4
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 149 publications
(135 citation statements)
references
References 55 publications
4
126
4
1
Order By: Relevance
“…Clinicians should look forward to the threshold of motor proficiency that is considered as a reasonable target for increasing physical activity. Researchers [26][27][28] studied the role of robot-assisted rehabilitation on functional recovery and showed the improvement of coordination. Liao et al [26] studied the effect of robot-assisted upper limb rehabilitation on daily functional recovery in patients with chronic stroke.…”
Section: Discussionmentioning
confidence: 99%
“…Clinicians should look forward to the threshold of motor proficiency that is considered as a reasonable target for increasing physical activity. Researchers [26][27][28] studied the role of robot-assisted rehabilitation on functional recovery and showed the improvement of coordination. Liao et al [26] studied the effect of robot-assisted upper limb rehabilitation on daily functional recovery in patients with chronic stroke.…”
Section: Discussionmentioning
confidence: 99%
“…In particular, it was highlighted that specific and repetitive tasks are most effective in acceleration of neuroplasticity of the brain (Hubbard et al 2009;Timmermans et al 2010). Liao et al (2012) reported that repetitive robot-assisted upper limb rehabilitation can After 4 weeks of robot-assisted reach training for 3 directions, significant improvement on upper extremity kinematic performance (movement velocity) was observed in individuals with chronic stroke (P < 0.05). Interestingly, upper extremity kinematic performance (movement velocity) for 3 directions showed highest improvement after 2 weeks of intervention.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies showed [56,57] that, even if patients accomplish the rehabilitation tasks in a good way during the therapy sessions, they are not able to repeat the same movements in real life situations. This happens especially for patients with cognitive deficits, because they are not able to relate the movement they perform under clinical conditions to the ones associated with activities in daily life (ADL).…”
Section: Patient's Virtualizationmentioning
confidence: 99%